"Cultural distance" among speakers of the same language - Gómez Parra, Elena (Sens public, 2009)
According to Byram (1997), intercultural competence means to be able to interact efficiently with persons from various countries in a foreign language. The paper introduces a new concept, in a sensible disaccord with this definition, the concept od « cultural distance » that exists between persons speaking the same language but do not share the same cultural values. We will introduce examples to illustrate some cases of a large cultural distance between speakers of the same language (in this case, Spanish).